Scaling Up Orange-fleshed Sweetpotato Through Agriculture and Nutrition (SUSTAIN) in Mozambique - International Potato Center (2016)
Since April 2014, 28,335 households have received OFSP vines in three provinces. In mid- 2016, ZebraFarm started the production of OFSP juice and OFSP-soy biscuits and Padaria Papú started baking OFSP bread and Swiss rolls. Efforts to increase urban demand for OFSP roots in Maputo City, the capital, are beginning to pay off.